GROWTH RESPONSES OF PALM SEEDLINGS TO DIFFERENT LIGHT INTENSITIES STIMULATING CANOPY GAPS WITH AN ECOPHYSIOLOGICAL APPROACH - DIAN LATIFAH; ROBERT A; CONGDON; JOSEPH A; HOLTUM (Reinwardtia, 2016)
LATIFAH, D., CONGDON, R. A. & HOLTUM, J. A. 2016. Growth responses of palm seedlings to different light intensities stimulating canopy gaps with an ecophysiological approach. Reinwardtia 15(2): 81 – 98. — Palms (Arecaceae) mainly grow in rainforests and many occur in disturbed areas like canopy gaps created by natural disturbances such as cyclones in Australia. Knowledge of seedling growth in different light intensities is essential to assist rainforest restoration in disturbed or marginal lands. The aim of this research was to investigate the effects of different light intensities on the seedling growth of Arenga australasica (H. Wendl. & Drude) S. T. Blake ex H. E. Moore, Calamus australis Mart., C. moti F. M. Bailey, Hydriastele wendlandiana (F. Muell.) H. Wendl. & Drude and Licuala ramsayi (F. Muell.) H. Wendl. & Drude. Seedling growth experiments (pot trials) were conducted in a glass house using shade cloth providing four different levels of shading: 59, 29, 17 and 6% sunlight. The growth rate, leaf turnover, leaf area, total chlorophyll, chlorophyll a:b ratio, vigor, above-ground and below-ground biomass and growth indices (LAR, SLA and LWR) of palm seedlings were measured. As a result of these measurements the relative shade tolerance of the five species was determined. The seedlings of Arenga australasica were classified as intermediate-shade intolerant species. Hydriastele wendlandiana seedlings were shade-intolerant. Calamus australis and C. moti seedlings are intermediate-shade intolerant. Licuala ramsayi seedlings were found to be a shade-tolerant.